Reorientasi Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Narkotika - Alhakim, Abdurrakhman; Manurung, Intan Feronika; Tantimin, Tantimin (Legal Spirit, 2024)
This study aims to review the legal aspects or legal reorientation towards children who are determined as perpetrators of narcotics crimes in Indonesia. This research is very important to be carried out conceptually to be able to provide measurable firm sanctions in accordance with the provisions of the Law on Narcotics and the Law on the Juvenile Criminal Justice System. This research is a normative juridical research using primary legal materials and secondary legal materials. The results of the study found that re-orientation of the legal aspects of children as perpetrators of narcotics crimes is very important to do because there is ambiguity related to the process of punishing children as drug offenders. First, the use of the Law on Narcotics as a basic object is still borne by the perpetrator in accordance with the stipulated articles, evidence that results in criminal sanctions according to the provisions. Second, for minors, the defense is still carried out in accordance with the Law on the Juvenile Criminal Justice System, where there is a reduction in sanctions that take into account the mental and physical condition of the child. When the verdict has been determined, the offender must be placed in a special correctional institution for children and given the right to medical rehabilitation and social rehabilitation because they consider the child's future. Third, the rehabilitation aspect can be prioritized as is the case when children are only designated as victims, or there is no evidence against them as the main perpetrators of Narcotics.